Risk Assessment of the Impact of Heavy Metals in Urban Traffic Dust on Human Health - Nima Mahmoud (19365472) (2023)
Excessive exposure to heavy metals induces potential adverse health impacts in humans. More specifically, heavy metals in particulate matter (PM) have a significant impact since PM can penetrate human organs and systems, causing several morbidities. In this work, dust samples were collected from 20 different types of roads in a busy zone in Doha during the winter of 2016–2017, where a higher human exposure rate occurs due to extensive outdoor activities during this time of the year. The elemental composition in terms of the mass concentration of 30 elements was determined in each sample via an energy-dispersive X-ray fluorescence (XRF) spectrometer. Then, the toxicity of six heavy metals in these airborne traffic dust samples was investigated. The heavy metals reported to have a hazardous impact on human health are As, Pb, Hg, Cd, Cr, Co, Ni, Cu, and Zn. The extent of carcinogenic and non-carcinogenic risk impact was assessed using pollution indices and then determining the health risks associated with exposure to heavy metals through inhalation, ingestion, and dermal contact. The non-carcinogenic hazard index analysis results indicate no toxicity for all metals. However, the carcinogenic risk factor results show that only chromium might induce a slight risk for children and adults. In light of this, further research is recommended to investigate more areas in urban Doha where more samples can be collected and analyzed. Other Information Published in: Atmosphere License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/atmos14061049